2014
DOI: 10.1186/1472-6823-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term auxological and endocrinological evaluation of patients with 9p trisomy: a focus on the growth hormone-insulin-like growth factor-I axis

Abstract: BackgroundTrisomy 9p is an uncommon anomaly characterised by mental retardation, head and facial abnormalities, congenital heart defects, kidney abnormalities, and skeletal malformations. Affected children may also show growth and puberty retardation with delayed bone age. Auxological and endocrinological data are lacking for this syndrome.MethodsWe describe three girls and one boy with 9p trisomy showing substantial growth failure, and we evaluate the main causes of their short stature.ResultsThe target heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 27 publications
1
21
0
17
Order By: Relevance
“…Previous studies have found that dup(9p) could be the result of the recombination events between homologous repeats in this region [Krepischi and Vianna, 2003]. Clinical severity in trisomy 9p generally correlates with the extent of the trisomic chromosome region; duplication of 9pterp11 is associated with milder dysmorphism, whereas duplication of 9p21.1q22-32 is associated with more severe craniofacial features [Stagi et al, 2014]. It seems that the 9p22 region is responsible for the principal phenotype observed in dup(9p) [Haddad et al, 1996].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have found that dup(9p) could be the result of the recombination events between homologous repeats in this region [Krepischi and Vianna, 2003]. Clinical severity in trisomy 9p generally correlates with the extent of the trisomic chromosome region; duplication of 9pterp11 is associated with milder dysmorphism, whereas duplication of 9p21.1q22-32 is associated with more severe craniofacial features [Stagi et al, 2014]. It seems that the 9p22 region is responsible for the principal phenotype observed in dup(9p) [Haddad et al, 1996].…”
Section: Discussionmentioning
confidence: 97%
“…Partial duplication of 9p is one of the most commonly detected autosomal structural abnormalities in liveborn infants [Di Bartolo et al, 2012;Stagi et al, 2014]. In most cases, it is due to different types of translocations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A potential explanation may be that this is a relatively poor gene region, so it may be more compatible with survival. [1][2][3] Trisomy 9p accounts for the fourth most frequent autosomal trisomy, after trisomies 21, 18, and 13. 2,4 It was first described in 4 patients by Rethoré et al in 1970 [1][2][3][4][5] and then outlined by Centerwall and Beatty-DeSana in 1975.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is a clinically recognizable entity and, to date, more than 200 cases have been reported in the bibliography. [1][2][3][4][5][6] It is characterized by the complete (Figure 1) or partial duplication of 9p. 2 Treatment with recombinant human growth hormone may be considered in patients with trisomy 9p with short stature, while taking into account the severity of intellectual disability and the potential for social inclusion.…”
Section: Introductionmentioning
confidence: 99%